IMF Research Perspectives : Spring-Summer 2019. (IMF Research Bulletin; IMF Research Bulletin ;, 2019)
The Spring-Summer 2019 issue of the IMF Research Perspectives explores how technology deals with old questions. Articles discuss the ways technological progress and the increased availability of data have helped in some areas, while presenting new challenges for analyzing various matters. The issue also includes an interview with Gita Gopinath, the new director of the IMF Research Department.